Preparation method of PET-based composite copper foil

By constructing a rough structure of poly(γ-benzyl-L-glutamate) nanorods on the surface of PET film and forming chemical bonds to bind to hydrogen bonds, the problem of poor bonding of PET-based composite copper foil is solved, and stronger interface combination effect.

CN119391031AInactive Publication Date: 2025-02-07深圳市国钠科技有限公司

Patent Information

Application Number
CN202411462605.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The PET-based composite copper foil has the problem that the interface bond between the copper plating and the PET matrix is ​​not ideal.

Method used

Poly(γ-benzyl-L-glutamate) nanorods were used to construct a rough structure on the surface of the PET film, and a good interface was formed with the PET film through chemical bonding and hydrogen bonding, and then electroless copper plating was performed.

Benefits of technology

The interface bonding strength between the copper plating and the PET film is improved, the peeling force between the plating and the PET film is increased, and the interface bonding effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391031A_ABST
    Figure CN119391031A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite current collector materials, and provides a preparation method of a PET-based composite copper foil. The method comprises the following steps: (1) dropwise adding concentrated sulfuric acid into a xylene dispersion liquid of a poly (gamma-benzyl-L-glutamate) nanorod, spraying onto the surface of a PET film, standing for reaction, and performing vacuum drying; (2) spraying an acetic acid solution of hydrobromic acid to the surface of the PET film, standing for reaction, washing and vacuum drying; (3) soaking the PET film in ammonia water, soaking the PET film in a silver nitrate solution, and soaking the PET film in a formaldehyde solution; and (4) chemical copper plating. The method not only can improve the interface bonding between the PET base film and the copper plating layer, but also has good environmental protection property and economical efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite current collector materials and provides a method for preparing a PET-based composite copper foil. Background Art

[0002] In the electrode structure of lithium batteries, the current collector is an important component, which is used to load electrode materials, collect current, transmit electrons, etc., and has a huge impact on the internal resistance and cycle performance of lithium batteries. Aluminum foil is a commonly used positive electrode current collector, and copper foil is a commonly used negative electrode current collector.

[0003] In order to comply with the development trend of high energy density and low cost of lithium batteries, copper foil is developing towards ultra-lightness, high density, high tensile strength and high elongation, and a new type of composite copper foil has emerged. Composite copper foil adopts a "sandwich" structure, which is mainly made of polymer films such as PET, PP, PI as the intermediate substrate, and copper metal is deposited on the upper and lower sides. Compared with traditional copper foil, composite copper foil has the advantages of high energy density, high cycle life, high safety, low cost and strong compatibility, and has become an important development direction for negative electrode current collectors.

[0004] PET substrate has good heat resistance and physical properties. The preparation of PET-based composite copper foil can deposit copper metal on the surface of PET film by physical vapor deposition, electroplating, chemical plating, etc. It is well known that plastic-based composite copper foil usually has the disadvantage of poor interface bonding between the metal coating and the plastic substrate. Compared with PP, the bonding between PET and the metal coating is slightly better, but it still needs to be improved.

[0005] The Chinese invention patent with patent application number 202311427130.9 discloses a micro-nano PET carrier composite electrolytic copper foil for lithium battery and its preparation and application. First, a Cu-Ni binary alloy layer is sputtered on the surface of the PET film using magnetron sputtering technology to obtain a carrier foil; then, copper is electrodeposited on the carrier foil using electrodeposition technology to thicken it, and finally, a new type of efficient post-treatment agent is used to obtain a micro-nano PET carrier composite electrolytic copper foil for lithium battery.

[0006] The Chinese invention patent with patent application number 202310691155.3 discloses a PET copper foil, chemical plating preparation method and its application. The PET film is roughened by degreasing, and the surface is modified by dopamine self-polymerization under ultraviolet radiation to form a tightly attached cross-linked composite layer, and establish covalent and non-covalent interactions with the organic-inorganic surface; then the hyperbranched polymer assists the metal deposition without palladium activation, and finally ultrasound-assisted chemical copper plating. Summary of the invention

[0007] It can be seen that the PET-based composite copper foil has the disadvantage that the interface bonding between the copper plating layer and the PET substrate is not ideal. In view of this, the present invention provides a preparation method of the PET-based composite copper foil to overcome the above disadvantages.

[0008] The specific technical solutions involved in the present invention are as follows:

[0009] The present invention provides a method for preparing a PET-based composite copper foil, comprising the following specific steps:

[0010] (1) adding concentrated sulfuric acid to a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, spraying the dispersion evenly onto the surface of a PET film, standing the dispersion at 70-90° C. for 18-24 h, and vacuum drying the dispersion;

[0011] (2) spraying a hydrobromic acid-acetic acid solution evenly onto the surface of the PET film, leaving it to stand for 3-5 hours to remove the benzyl group, washing it with a sodium bicarbonate solution and deionized water in sequence, and drying it in a vacuum;

[0012] (3) first immerse the PET film in ammonia water, then immerse it in a silver nitrate solution, and then immerse it in a formaldehyde solution;

[0013] (4) Chemical copper plating is performed on the PET film.

[0014] Preferably, in step (1), the diameter of the poly(γ-benzyl-L-glutamate) nanorods is 50-200 nm, and the aspect ratio is 3-5:1.

[0015] Preferably, in step (1), the concentration of concentrated sulfuric acid is 98 wt %, and the amount added is 0.05-0.1 % of the mass of the dispersion.

[0016] Preferably, in step (1), the concentration of the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods is 10-20 g / L; further preferably, the spraying amount is 10-20 g / m 2 .

[0017] Preferably, in step (2), the concentration of the hydrobromic acid acetic acid solution is 30-50wt%; further preferably, the spraying amount is 20-40g / m 2 .

[0018] Preferably, in step (3), the concentration of the ammonia solution is 20-25wt%, and the soaking time is 1-2min; the concentration of the silver nitrate solution is 1-1.5g / L, and the soaking time is 3-5min; the concentration of the formaldehyde solution is 36-40wt%, and the soaking time is 10-15min.

[0019] Preferably, in step (4), the electroless copper plating solution comprises 8-10 g / L copper sulfate, 15-20 g / L disodium ethylenediaminetetraacetic acid, 10-15 ml / L formaldehyde solution (concentration 36-40 wt%), and the pH value is adjusted to 12-13 with sodium hydroxide; further preferably, the plating temperature is 40-45° C. and the time is 30-40 min.

[0020] As is known, poly(γ-benzyl-L-glutamate) is a polymer obtained by polycondensation of γ-benzyl-L-glutamate monomers, and its structural formula is shown in the attached figure. Figure 1 As shown, it can be seen that there are a large number of amide groups on the main chain of the molecule, and the terminal groups are carboxyl and amino groups. Poly(γ-benzyl-L-glutamate) can be self-assembled into nanorod-like structures under the conditions of dissolution in a specific organic cosolvent (tetrahydrofuran / N,N-dimethylformamide) and precipitation in a selective solvent (water).

[0021] The present invention sprays a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods on the surface of a PET film, and the nanorods are deposited on the film surface to construct a surface roughness structure. In addition, since the two ends of the PET molecular chain contain carboxyl and / or hydroxyl groups, and the two ends of the poly(γ-benzyl-L-glutamate) molecular chain contain carboxyl and amino groups, under heating conditions and the catalysis and dehydration of concentrated sulfuric acid, esterification or amidation reactions can occur between the end groups of the two to form chemical bonds, and can also form interactions through hydrogen bonds. Therefore, after step (1), the poly(γ-benzyl-L-glutamate) nanorods construct a roughness structure on the surface of the PET film, and can form a good interface with the PET film through chemical bonds and hydrogen bonds.

[0022] Furthermore, the benzyl group of poly(γ-benzyl-L-glutamate) was removed by using an acetic acid solution of hydrobromic acid, so that the ester group on the side chain was converted into a carboxyl group, which significantly improved the hydrophilicity of the PET film surface. Then, the silver ions were adsorbed on the surface of the PET film by using the good complexing ability of the carboxyl group for silver ions and reduced to silver particles by formaldehyde, which served as the catalytic center for subsequent chemical copper plating.

[0023] The invention provides a preparation method of a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, which specifically comprises the following steps: dissolving poly(γ-benzyl-L-glutamate) in a tetrahydrofuran / N,N-dimethylformamide mixed solvent, slowly adding ultrapure water under magnetic stirring, and then ultrapure dialyzing the ultrapure water for 3 days to obtain a water dispersion of the poly(γ-benzyl-L-glutamate) nanorods, freeze-drying to remove water, and adding xylene for ultrasonic dispersion to obtain a xylene dispersion of the poly(γ-benzyl-L-glutamate) nanorods.

[0024] In the preparation process of the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, preferably, the dosage ratio of poly(γ-benzyl-L-glutamate), tetrahydrofuran, N,N-dimethylformamide and ultrapure water added is 1g:1L:9L:3L.

[0025] The present invention provides a method for preparing a PET-based composite copper foil, which has the following beneficial effects:

[0026] First, the present invention uses poly (γ-benzyl-L-glutamate) nanorods to construct a rough structure on the surface of a PET film, and the nanorods form a good interface bond with the PET film. The cross section of the nanorods is circular (or nearly circular), and after being deposited on the surface of the PET film, a convex structure is formed. During chemical copper plating, copper can be deposited not only on the front side of the nanorods (the part that can be seen when facing the PET film), but also on the back side of the nanorods (the part that cannot be seen when facing the PET film). When the copper deposition fills the rough structure, the nanorods have a spatial anchoring effect on the copper on the back side, which can increase the peeling force of the coating and the PET film, thereby improving the interface bond.

[0027] Second, after the benzyl group of poly(γ-benzyl-L-glutamate) nanorods is removed, many carboxyl groups are generated on the side chains of the polymer, which significantly improves the hydrophilicity of the PET film surface and is conducive to forming a good interface bonding with the metal layer.

[0028] Third, since the nanorods have a high specific surface area, the carboxyl complexed silver ions on the surface of the nanorods can increase the loading area for silver ions, thereby increasing the catalytic active centers of chemical copper plating and increasing the copper deposition area, thereby improving interface bonding.

[0029] Fourth, the traditional chemical copper plating requires the plastic substrate to be roughened and activated before treatment, usually using chromium-containing roughening solution, palladium colloid activation solution, etc., which is highly polluting and costly. The method of the present invention uses nanorods to form a rough, hydrophilic surface, and uses silver, which is cheaper than palladium, so it is more environmentally friendly and economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the structural formula of poly(γ-benzyl-L-glutamate). DETAILED DESCRIPTION

[0031] The present invention is further described in detail below through specific embodiments, but this should not be construed as limiting the scope of the present invention to the following examples. Without departing from the above-mentioned method concept of the present invention, various substitutions or changes made according to common technical knowledge and conventional means in the art should be included in the scope of the present invention.

[0032] First, a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods was prepared as follows:

[0033] Poly(γ-benzyl-L-glutamate) was dissolved in a tetrahydrofuran / N,N-dimethylformamide mixed solvent, and ultrapure water was slowly added under magnetic stirring, and then ultrapure dialyzed with ultrapure water for 3 days to obtain an aqueous dispersion of poly(γ-benzyl-L-glutamate) nanorods, freeze-dried to remove water, and xylene was added for ultrasonic dispersion to obtain a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods. The dosage ratio of poly(γ-benzyl-L-glutamate), tetrahydrofuran, N,N-dimethylformamide, and ultrapure water added was 1g:1L:9L:3L. The concentration of the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods was 15g / L.

[0034] The number average molecular weight of the poly(γ-benzyl-L-glutamate) used was 1.9×10 5 The diameter of the poly(γ-benzyl-L-glutamate) nanorods self-assembled by the above process is 150±20 nm and the length is 550±50 nm.

[0035] Then, PET-based composite copper foil materials were prepared according to the methods of the following examples and comparative examples. The PET film used had a thickness of 5 μm and was purchased from Shijiazhuang Dajia New Material Technology Co., Ltd.

[0036] Example 1

[0037] (1) 98 wt % concentrated sulfuric acid was added dropwise to the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, and the mixture was sprayed evenly onto the surface of the PET film. The mixture was allowed to stand at 80° C. for 18 h and then dried under vacuum. The amount of concentrated sulfuric acid added was 0.1% of the mass of the dispersion. The amount of the dispersion sprayed was 10 g / m 2 ;

[0038] (2) Spray a 40 wt % hydrobromic acid solution in acetic acid onto the surface of the PET film, let it stand for 3.5 h to remove the benzyl group, wash it with sodium bicarbonate solution and deionized water in turn, and dry it in vacuum; the spraying amount is 20 g / m 2 ;

[0039] (3) first soaking the PET film in 25 wt % ammonia water for 1 min, then soaking it in 1.3 g / L silver nitrate solution for 3 min, and then soaking it in 36 wt % formaldehyde solution for 10 min;

[0040] (4) The PET film was subjected to chemical copper plating; the plating solution composition included 9 g / L copper sulfate, 18 g / L disodium ethylenediaminetetraacetic acid, 12 ml / L formaldehyde solution (concentration 36 wt%), and the pH value was adjusted to 12.5 with sodium hydroxide; the plating temperature was 40° C. and the time was 35 min.

[0041] Example 2

[0042] (1) 98 wt % concentrated sulfuric acid was added dropwise to the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, and the mixture was sprayed evenly onto the surface of the PET film. The mixture was allowed to stand at 80° C. for 21 h and then dried under vacuum. The amount of concentrated sulfuric acid added was 0.1% of the mass of the dispersion. The amount of the dispersion sprayed was 15 g / m 2 ;

[0043] (2) Spray a 40 wt % hydrobromic acid solution in acetic acid onto the surface of the PET film, let it stand for 4 h to remove the benzyl group, wash it with sodium bicarbonate solution and deionized water in turn, and dry it in vacuum; the spraying amount is 30 g / m 2 ;

[0044] (3) first soaking the PET film in 25 wt % ammonia water for 1.5 min, then soaking it in 1.3 g / L silver nitrate solution for 4 min, and then soaking it in 36 wt % formaldehyde solution for 12 min;

[0045] (4) The PET film was subjected to chemical copper plating; the plating solution composition included 9 g / L copper sulfate, 18 g / L disodium ethylenediaminetetraacetic acid, 12 ml / L formaldehyde solution (concentration 36 wt%), and the pH value was adjusted to 12.5 with sodium hydroxide; the plating temperature was 40° C. and the time was 35 min.

[0046] Example 3

[0047] (1) 98 wt % concentrated sulfuric acid was added dropwise to the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, and the mixture was sprayed evenly onto the surface of the PET film. The mixture was allowed to stand at 80° C. for 24 h and then dried under vacuum. The amount of concentrated sulfuric acid added was 0.1% of the mass of the dispersion. The amount of the dispersion sprayed was 20 g / m 2 ;

[0048] (2) Spray a 40 wt % hydrobromic acid solution in acetic acid onto the surface of the PET film, let it stand for 4.5 h to remove the benzyl group, wash it with sodium bicarbonate solution and deionized water in turn, and dry it in vacuum; the spraying amount is 40 g / m 2 ;

[0049] (3) first soaking the PET film in 25 wt % ammonia water for 2 min, then soaking it in 1.3 g / L silver nitrate solution for 5 min, and then soaking it in 36 wt % formaldehyde solution for 15 min;

[0050] (4) The PET film was subjected to chemical copper plating; the plating solution composition included 9 g / L copper sulfate, 18 g / L disodium ethylenediaminetetraacetic acid, 12 ml / L formaldehyde solution (concentration 36 wt%), and the pH value was adjusted to 12.5 with sodium hydroxide; the plating temperature was 40° C. and the time was 35 min.

[0051] Comparative Example 1

[0052] Step (1): Instead of using a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, poly(γ-benzyl-L-glutamate) that has not been assembled into nanorods is directly added to xylene and sprayed. Other raw materials and processes are the same as those in Example 3.

[0053] Steps (2)-(4): Same as Example 3.

[0054] Comparative Example 2

[0055] The conventional method is used to perform chemical copper plating on the surface of the PET film, specifically:

[0056] (1) Roughening: The PET film was treated with an aqueous solution of 350 g / L chromium trioxide and 350 g / L sulfuric acid at 60 °C for 15 min;

[0057] (2) Neutralization: Treat with 60 g / L sodium hydroxide solution at room temperature for 1 min;

[0058] (3) Sensitization and activation: using a 12 wt % hydrochloric acid solution containing 0.1 g / L palladium chloride and 10 g / L stannous chloride for treatment at room temperature for 25 min;

[0059] (4) Degumming: using an aqueous solution containing 35 g / L of sodium hydroxide for 3 min at room temperature;

[0060] (5) Chemical copper plating: same as in Example 3.

[0061] Performance test: The bonding strength between the coating and the PET base film was tested by the 90° bonding strength test method to characterize the interface bonding between the two. Specifically, use a sharp blade to make two parallel scratches (1 cm spacing) on ​​the surface of the coating to expose the PET substrate, peel off 1.5 mm of the coating along the scratches, use a universal material testing machine, put the peeling end into the fixture, adjust the movement speed of the moving clamp to 50 mm / min, start the testing machine, and allow the peeling end to continue to separate freely to obtain the bonding strength between the coating and the PET base film. The environmental conditions of the test are: temperature 23±2°C, relative humidity 65±5%. The test results are: the bonding strength between the coating and the PET base film of Examples 1-3 and Comparative Examples 1-2 are 5.76 N / cm, 6.49 N / cm, 6.91 N / cm, 5.88 N / cm, and 4.12 N / cm, respectively.

Claims

1. A method for preparing a PET-based composite copper foil, characterized in that: The specific steps include: (1) adding concentrated sulfuric acid to a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods, spraying the dispersion evenly onto the surface of a PET film, standing the dispersion at 70-90° C. for 18-24 h, and vacuum drying the dispersion; (2) spraying a hydrobromic acid-acetic acid solution evenly onto the surface of the PET film, leaving it to stand for 3-5 hours to remove the benzyl group, washing it with a sodium bicarbonate solution and deionized water in sequence, and drying it in a vacuum; (3) first immerse the PET film in ammonia water, then immerse it in a silver nitrate solution, and then immerse it in a formaldehyde solution; (4) Chemical copper plating is performed on the PET film.

2. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: In step (1), the diameter of the poly(γ-benzyl-L-glutamate) nanorods is 50-200 nm, and the aspect ratio is 3-5:

1.

3. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: In step (1), the concentration of concentrated sulfuric acid is 98 wt %, and the amount added is 0.05-0.1 % of the mass of the dispersion.

4. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: In step (1), the concentration of the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods is 10-20 g / L; the spraying amount is 10-20 g / m 2 .

5. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: In step (2), the concentration of the hydrobromic acid acetic acid solution is 30-50wt%; the spraying amount is 20-40g / m 2 .

6. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: In step (3), the concentration of ammonia solution is 20-25wt%, and the soaking time is 1-2min; the concentration of silver nitrate solution is 1-1.5g / L, and the soaking time is 3-5min; the concentration of formaldehyde solution is 36-40wt%, and the soaking time is 10-15min.

7. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: In step (4), the electroless copper plating solution comprises 8-10 g / L copper sulfate, 15-20 g / L disodium ethylenediaminetetraacetic acid, 10-15 ml / L formaldehyde solution (concentration 36-40 wt%), and the pH value is adjusted to 12-13 with sodium hydroxide; the plating temperature is 40-45° C., and the time is 30-40 min.

8. The method for preparing a PET-based composite copper foil according to claim 1, characterized in that: The preparation method of the xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods is as follows: poly(γ-benzyl-L-glutamate) is dissolved in a tetrahydrofuran / N,N-dimethylformamide mixed solvent, ultrapure water is slowly added dropwise under magnetic stirring, and then ultrapure water is dialyzed for 3 days to obtain an aqueous dispersion of poly(γ-benzyl-L-glutamate) nanorods, freeze-dried to remove water, and xylene is added for ultrasonic dispersion to obtain a xylene dispersion of poly(γ-benzyl-L-glutamate) nanorods.

9. The method for preparing a PET-based composite copper foil according to claim 8, characterized in that: The usage ratio of poly(γ-benzyl-L-glutamate), tetrahydrofuran, N,N-dimethylformamide, and ultrapure water added dropwise is 1 g:1 L:9 L:3 L.

Citation Information

Patent Citations

  • PET copper foil, chemical plating preparation method and application thereof

    CN116607134A

  • Micro-nano PET carrier composite electrolytic copper foil for lithium battery as well as preparation and application of micro-nano PET carrier composite electrolytic copper foil

    CN117448909A

Cited By

  • Method for preparing ultrathin high-ductility copper foil by compounding electrolysis and rolling

    CN121732596A